Comparison on distribution and abundance of order odonata between Sg. Muar and Ulu Bendul In Kuala Pilah, Negeri Sembilan / Nurul Hazwanie Abdul Rahim - Abdul Rahim, Nurul Hazwanie (2018)
A study was conducted to investigate the distribution and abundance and to determine the species diversity of order Odonata at Sg. Muar and Ulu Bendul in Kuala Pilah, Negeri Sembilan. A total of 66 individuals were observed which belong to 5 families; 1 family from suborder of Anisoptera (Libellulidae) and 4 families from suborder of Zygoptera (Chlorocyphidae, Calopterygidae, Platycnemididae and Coenagrionidae). The family of Libellulidae was the major specimen found in both study sites with 50 individuals followed by Chlorocyphidae with 6 individuals, Calopterygidae with 5 individuals, Platycnemididae with 4 individuals and lastly, with only one individual only of Coenagrionidae. The data had been analyzed by using the Margalef index (R), Shannon-Weiner index (H’) and Evenness index (E). (R) for Sg. Muar was 11.73 while (R) for Ulu Bendul was 10.69. (H’) for Sg. Muar was 2.06 and (H’) for Ulu Bendul was 2.00. (E) value for Sg. Muar was 0.83 whereas (E) for Ulu Bendul was 0.82. The SQ value for both sites was 0.52 or 52% which means both sites had slightly similar regarding their species composition of distribution and abundance of odonates.